2016
DOI: 10.1016/j.eatbeh.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Is night eating syndrome associated with obstructive sleep apnea, BMI, and depressed mood in patients from a sleep laboratory study?

Abstract: Purpose To assess night eating syndrome (NES) in patients referred for polysomnography and its association with obstructive sleep apnea (OSA). We also assessed whether participants with OSA were more likely to get up and eat at night, and whether these behaviors were associated with the apnea-hypopnea sleep index (AHI). We additionally examined whether NES and OSA were associated with BMI, and assessed depressed mood among participants with NES or OSA. Methods The Night Eating Diagnostic Questionnaire (NEDQ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 50 publications
(58 reference statements)
0
24
2
Order By: Relevance
“…Geliebter et al reported that the people with night-eating syndrome were more likely to have a depressed mood than those without the syndrome, by using univariate analysis. 7 A cross-sectional study including 404 Korean nurses indicated that those with night-eating syndrome were 1.65 times more likely to have a greater severity of depressive symptoms than those without the syndrome. 17 Another observational study investigated the prevalence of night-eating syndrome among patients with major depression and clinical differences between patients with and without night-eating syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geliebter et al reported that the people with night-eating syndrome were more likely to have a depressed mood than those without the syndrome, by using univariate analysis. 7 A cross-sectional study including 404 Korean nurses indicated that those with night-eating syndrome were 1.65 times more likely to have a greater severity of depressive symptoms than those without the syndrome. 17 Another observational study investigated the prevalence of night-eating syndrome among patients with major depression and clinical differences between patients with and without night-eating syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Geliebter et al reported that the subjects with night-eating syndrome, primarily an eating disorder, were more likely to have a depressed mood. 7 Most recently, a study of 301 Italian non-clinical adolescents aged 15-19 years indicated a significant association between nighteating syndrome and depressive symptoms. 8 We previously reported that habitual snacking after dinner was significantly associated with the incidence of depressive symptoms in Japanese middle-aged adults during a 2-year follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…25 On the other hand, another study was unable to find the positive link between the nocturnal eating and increased BMI but did find positive association between nocturnal eating and depression. 26 Nocturnal eaters suffer from disturbed and short sleep cycles. 27,28 Disturbed and short sleep cycles are themselves an independent predisposing factors for increased BMI.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between NES and OSA is not straightforward, as explorative studies have produced partially divergent results [66][67][68]. Generally, the frequency of sleep-related eating disorders is not directly associated with the severity of OSA, measured by the apnea/hypopnea index (AHI).…”
Section: Nes and Coexistent Sleep Disordersmentioning
confidence: 99%